(untitled) - Jeremy, David J. (Cambridge Massachusetts, 1981)
The book examines the transfer of four specific technologies: cotton spinning, powerloom weaving, calico printing, and woollen manufacturing. These technologies all made successful transatlantic crossings in spite of the institutional and technical barriers to transfer that Jeremy describes, including industrial secretiveness, the English patent search system, the paucity of technical publications, the prohibitory laws, artisan resistance to technica change, variations in local technical traditions, and changes in the pace and direction of invention.
Keywords: Chuyển giao công nghệ,Technology transfer; Lịch sử,History